2015
DOI: 10.1111/ijfs.12911
|View full text |Cite
|
Sign up to set email alerts
|

Effect of physical and thermal processing upon benzylglucosinolate content in tubers of the Brassicaceae maca (Lepidium meyenii) using a novel rapid analytical technique

Abstract: Benzylglucosinolate (BG) was extracted by 70% methanol from maca and purified on acidic alumina column and semi-preparative Cosmosil cholester column. The purified sample was verified as BG by electrospray ionisation mass spectrometry (ESI-MS) and nuclear magnetic resonance spectra. The purity was 98.3% as determined by HPLC-MS. BG content of maca was quantified using external standard method by HPLC. Effect of physical and thermal processing on BG content of maca was investigated. When maca was steamed for 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Our previous work showed that the concentration of macamides was significantly different in maca treated with different drying processes, especially steaming, which led to a significant loss of macamides . In contrast, there was no significant change in benzyl isothiocyanate content when maca was treated with steam . This suggests that the accumulation of macamides in dry hypocotyls is related to benzyl isothiocyanate during the drying process.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Our previous work showed that the concentration of macamides was significantly different in maca treated with different drying processes, especially steaming, which led to a significant loss of macamides . In contrast, there was no significant change in benzyl isothiocyanate content when maca was treated with steam . This suggests that the accumulation of macamides in dry hypocotyls is related to benzyl isothiocyanate during the drying process.…”
Section: Resultsmentioning
confidence: 96%
“…19 In contrast, there was no significant change in benzyl isothiocyanate content when maca was treated with steam. 20 This suggests that the accumulation of macamides in dry hypocotyls is related to benzyl isothiocyanate during the drying process. Even so, macamide profiling still revealed regional differences when samples were dried in the same way.…”
Section: Different Geographical Origins and Colours For Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…The RnormalPred2 value of 0.9172 was in line with the RnormalAdj2 value of 0.8878. Generally, the lower the value of coefficient variation (CV), which illustrates the degree of precision, the higher the experiment reliability (Li et al ., ,b). In this study, the CV value (1.79%) showed that the experiments were precise and reliable.…”
Section: Resultsmentioning
confidence: 97%
“…Physicochemical properties were determined using the following methods: Molisch test (Karnpanit et al ., ), iodination reaction (Li et al ., ,b), Fehling's test, FeCl 3 reaction, ultraviolet (UV) analysis. In addition, the components of polysaccharide and proteins were determined by the phenol‐sulphuric acid method (Zhang et al ., ) and the Bradford method (Gonçalves et al ., ), respectively.…”
Section: Methodsmentioning
confidence: 95%